Monolithic integration of InSb photodetector on silicon for mid-infrared silicon photonics - Jia, Bo Wen (2019)
The InSb photodetector on a Si substrate acts as a signal receiver for the mid-infrared silicon photonics application to overcome the limitation of group IV semiconductors. In this paper, we demonstrated an InSb p–i–n photodetector with an InAlSb barrier layer grown on (100) silicon substrates via a GaAs/Ge buffer by molecular beam epitaxy. The lattice mismatch between InSb and GaAs was accommodated by an interfacial misfit array. The 50% cutoff detectable wavelength of this detector increased from 5.7 μm at 80 K to 6.3 μm at 200 K. An 80 K detectivity of 8.8 × 109 cmHz1/2 W–1 at 5.3 μm was achieved with a quantum efficiency of 16.3%. The dark current generating mechanism of this detector is both generation–recombination and surface leakage above 140 K, while it is only surface leakage from 120 to 40 K.